Adults and Learning Disabilities: Moving Beyond the Limits of Learning - Linda Eastwick Covington (Adult Education Research Conference, 2004)
The heterogeneous nature of learning disabilities has led to confusion regarding their definition and their intervention. Although the law protects adults with learning disabilities both in the workplace and classroom, it provides only a broad definition that has been subject to many interpretations. There is a paucity of longitudinal research on learning disabilities, but one study indicates that they are ameliorated by certain protective factors. Cross-sectional research suggests that a wide variety of teaching techniques is necessary for classroom success. This research serves to inform adult educators of the dynamic concept of learning disabilities as well as effective classroom interventions.